Speaking, How To Improve This Competence? An Exploration Of Individual performance Task in Speaking Class - sih pratiwi, Dyah (Universitas Lancang Kuning, 2025)
Abstract The aim of this research is to know individual performance task improving students’ speaking skill in speaking class. Qualitative is the method of this research. Descriptive qualitative is presented in form table and diagram data. The samples of this research are students in speaking class one of the Universities in Bandar Lampung. There are 17 students who take speaking class. The data collecting technique used interviewed and documentation. The interviewed is used in this research in gaining the students’ opinion after doing speaking class using individual performance task. This research used unstructured interviewed. There are 13 questions as guide questions have given to the students. The documentation also used in this research that the score of speaking class.The result of interviewed there were 82% students improve in students’ self-confidence. 76% students claimed that they get improve in speaking technical skill. Learning independence of students also improve at 64% in percentage scale. The highest significant improvement is at learning strategies, there were 94% in percentage scale.Task effectiveness also one of issues got improving 70% in percentage scale. Task challenge was 58% in percentage scale. Hope and suggestion of students got 35% in percentage scale. Meanwhile, based on the documentation speaking score before and after doing individual performance task there were 21% improving of students’ speaking score. All of the data above, it can be shown that individual performance task can improve speaking skill in speaking class.